Tinjauan Kriminologis terhadap Praktik Ilegal Penangkapan dan Perdagangan Satwa Liar di Provinsi Lampung - Sharla Martiza Maulana P; Maya Shafira; Fristia Berdian Tamza (Lembaga Pengembangan Kinerja Dosen, 2025)
Illegal wildlife capture and trade is a form of crime that has a serious impact on environmental sustainability. This practice not only disrupts the balance of the ecosystem but also threatens the sustainability of biodiversity, a vital asset for the nation and the world. Lampung Province is a strategic region for wildlife trafficking due to its proximity to inter-island distribution routes. This condition makes Lampung one of the provinces with the highest number of wildlife confiscations in Indonesia, thus requiring increased attention from various parties. This study aims to analyze the factors causing illegal wildlife capture and trade, while also identifying mitigation efforts. The research method used is a combination of normative and empirical juridical. Data were obtained through literature review and interviews with relevant agencies, then analyzed qualitatively using an interactive approach and legal interpretation. The results show that economic factors, socio-cultural factors, education levels, environmental conditions, and hobby-based activities are the main triggers for the rise in wildlife crime. Economic motives often drive people to get involved due to the high selling price of wildlife, while socio-cultural factors and low legal awareness exacerbate the situation. An environment that supports fishing activities, along with demand from certain hobbies such as animal collecting, further increases the opportunity for violations. In response, the Lampung Regional Police, in collaboration with the Natural Resources Conservation Agency (BKSDA) SKW III Bengkulu-Lampung, have implemented penal measures through law enforcement, as well as non-penal measures through education, outreach, and community empowerment. This study concludes that synergy between law enforcement, active community participation, and sustainable prevention strategies is key to reducing the rate of wildlife crime. With integrated collaboration, it is hoped that biodiversity can be maintained for the sustainability of the ecosystem in the future.